The SECRET of the TREASURE KEEPERS - Howell, A. M., (Ann-Marie Howell) (London : Usborne Publishing Ltd., 2022)
"February 1948. Ruth has been whisked off to the lonely Rook Farm to investigate the discovery of long-buried treasure with her mother. But at the farmhouse, she finds secrets lurk around every corner. Joe, the farmer's son, is hiding something about the treasure, while land girl Audrey watches their every move. But before Ruth can find out more, the treasure is stolen... With a storm coming, Ruth must race to uncover the secrets of the treasure keepers before all of their lives are changed forever"--Publisher's description.
Keywords: Children's stories; Mothers and daughters -- Juvenile fiction